Financing of NCD Prevention in LMICs: Sri Lanka Case Study - Ammar Rashid; Kassim Nishtar; Saba Amjad (Journal of the Pakistan Medical Association, 2026)
Objective: To estimate spending on NCD prevention in Sri Lanka and identify the enablers, challenges and dynamics underpinning population-level NCD prevention spending, with particular focus on tobacco use, harmful use of alcohol, unhealthy diets and physical inactivity. Methods: Primary and secondary data collection was used to examine processes and organizational contexts that shape the formulation of policy and financial frameworks for NCD prevention. The methodology was categorized into three tiers; an academic literature review, scrutiny and analysis of official policy documents and budgetary data on health and NCDs, and in-depth stakeholder interviews with key government officials leading NCD programmes. Government and government-routed donor spending on population level prevention was gauged to estimate NCD prevention spending. Where possible, impact of prevention programmes on disease incidence and risk factors was gauged through available outcome indicators. Results: Sri Lanka allocated an estimated LKR 938.93 million on NCD prevention and health promotion in 2019, accounting for less than 1% of total public spending on health for the year. Enablers include tobacco control progress, improved primary care, institutions committed to NCD prevention including the Health Promotion Bureau, and political and civil society leadership. Challenges include persistent alcohol use, high levels of salt intake, pressure against regulations by the food and beverage industry, and lack of a countrywide physical activity campaign. Opportunities include earmarking excise taxes for health promotion, and strengthening primary level prevention. Conclusion: Sri Lanka has made considerable progress in reorienting its health system towards NCD prevention, but spending on NCD prevention still remains less than 1% of government health spending. Increased allocation of resources towards population-level NCD prevention can help address the growing NCD burden and create economic benefits. Keywords: Noncommunicable Diseases, Tobacco, Sodium Chloride, Employees, Incidence, Health, Diet, Exercise, Risk Factors, Beverages, Taxes